The Gurkhas the inside story of the world's most feared soldiers - Parker, John (Bounty, 2005)
The author has travelled in Nepal and met many Gurkhas to investigate the background to their traditional service to Britain and the threat that this is now under. He recounts famous battles when they collected VC's and earned admiration